(untitled) (Research, Society and Development, 2018)
The present article aims to analyze the importance and the economic and financial impact of garment factions in the Seridó region. Methodology to be applied, through the application of interviews with factional variables. As a result the result reveals that the industry is an important alternative for a generation of income in the region where the investment shortage is launched. Finally, the study concludes that the factions are largely concerned with being idle, with no prospect of work and income, on the margins of the labor market.